MGMT inactivation as a new biomarker in patients with advanced biliary tract cancers. Issue 14 (13th June 2022) - Niger, Monica; Nichetti, Federico; Casadei‐Gardini, Andrea; Morano, Federica; Pircher, Chiara; Tamborini, Elena; Perrone, Federica; Canale, Matteo; Lipka, Daniel B.; Vingiani, Andrea; Agnelli, Luca; Dobberkau, Anna; et al.
Abstract : Biliary tract cancers (BTCs) have poor prognosis and limited therapeutic options. The impact of O 6 ‐methylguanine‐DNA methyltransferase ( MGMT ) inactivation in advanced BTC patients is not established. We investigated the prevalence, prognostic, and predictive impact of MGMT inactivation in two multicenter cohorts. MGMT inactivation was assessed through PCR and immunohistochemistry (IHC) in an Italian cohort; the results were then externally validated using RNA sequencing (RNA‐seq) data from the BTC subcohort of the Molecularly Aided Stratification for Tumor Eradication Research (MASTER) precision oncology program of the National Center for Tumor Diseases Heidelberg and the German Cancer Consortium. Among 164 Italian cases, 18% presented MGMT promoter hypermethylation (> 14%) and 73% had negative MGMT protein expression. Both were associated with worse overall survival (OS; HR 2.31; P < 0.001 and HR 1.99, P = 0.012, respectively). In the MASTER cohort, patients with lower MGMT mRNA expression showed significantly poorer OS (median OS [mOS] 20.4 vs 31.7 months, unadjusted HR 1.89; P = 0.043). Our results suggest that MGMT inactivation is a frequent epigenetic alteration in BTC, with a significant prognostic impact, and provide the rationale to explore DNA‐damaging agents in MGMT ‐inactivated BTCs. Abstract : The impact of MGMT inactivation in patients with advanced biliary tract cancer (BTC) is not established. We investigated its prevalence, prognostic, and predictive impact, assessed through methylation‐specific PCR and IHC, in a large Italian cohort. Then we evaluated MGMT inactivation through RNA‐seq and DNA methylation analysis in an independent German cohort. Overall, MGMT inactivation or reduced expression consistently resulted in poorer survival.